18F-FDG PET/CT focal, but not osteolytic, lesions predict the progression of smoldering myeloma to active disease - Zamagni, Elena; Nanni, C.; Gay, F.; Pezzi, A.; Patriarca, F.; Bellò, M.; Rambaldi, I.; Tacchetti, P.; Hillengaß, Jens; Gamberi, B.; Pantani, L.; Magarotto, V.; et al. (Leukemia, 2016)
Identification of patient sub-groups with smoldering multiple myeloma (SMM) at high risk of progression to active disease (MM) is an important goal. 18F-FDG PET/CT (positron emission tomography (PET) integrated with computed tomography (PET/CT) using glucose labelled with the positron-emitting radionuclide 18F) allows for assessing early skeletal involvement. Identification of osteolytic lesions by this technique has recently been incorporated into the updated International Myeloma Working Group criteria for MM diagnosis. However, no data are available regarding the impact of focal lesions (FLs) without underlying osteolysis on time to progression (TTP) to MM. We hence prospectively studied a cohort of 120 SMM patients with PET/CT. PET/CT was positive in 16% of patients (1 FL: 8, 2 FLs: 3, >3 FLs: 6, diffuse bone marrow involvement: 2). With a median follow-up of 2.2 years, 38% of patients progressed to MM, in a median time of 4 years, including 21% with skeletal involvement. The risk of progression of those with positive PET/CT was 3.00 (95% confidence interval 1.58-5.69, P=0.001), with a median TTP of 1.1 versus 4.5 years for PET/CT-negative patients. The probability of progression within 2 years was 58% for positive versus 33% for negative patients. In conclusion, PET/CT positivity significantly increased the risk of progression of SMM to MM. PET/CT could become a new tool to define high-risk SMM.